Exploring the underlying structures of sustainability performance measures: a study of transportation projects in South Africa. Issue 8 (17th May 2022) - Okoro, Chioma Sylvia; Musonda, Innocent; Agumba, Justus Ngala
Abstract: Sustainability assessment of infrastructure projects aims at supporting the selection or maintenance of the best investment option among alternatives. However, there is no consensus on the indicators of sustainability performance of transportation projects especially during the planning stage of projects. The current study therefore investigated the underlying structure and thus minimum number of factors that can be used to assess transportation infrastructure sustainability. Using empirical data collected from a field questionnaire survey among 132 built environment professionals in South Africa, an exploratory factor analysis (EFA) was conducted to identify the underlying structure of theorised transportation project sustainability measures. Findings revealed a four-factor structure comprising infrastructure condition and impacts, user acceptability, financial management factors, as well as safety and security. The validity and reliability of these common factors were demonstrated. The four-factor solution is envisaged to be useful in ex-ante and ex-post evaluation of transportation infrastructure projects in order to ensure that such proposed and/or existing projects deliver intended objectives and benefits in the long run.